ANALISIS REALISME NEOKLASIK TERHADAP HUBUNGAN INDONESIA – TIONGKOK - Rizky Ihsan (Universitas Budi Luhur, 2018)
Foreign policy is a tool for countries to achieve certain outcomes, including how to deal with another country in the international arena. When viewing a rising power as a threat, they push for balancing strategy in order to keep a country in check. It is generally pursued by enhancing their own military capability, or by maintaining alliance with one another. This article aims to analyze Indonesia-China relations in Joko Widodo’s administration, where Jakarta tends to push for underbalancing strategy, as the political elites have different perceptions with one another as well as China’s ambivalence policy toward Indonesia. Based on neoclassical realism, underbalancing occurs when a country’s political elite is fragmented. In this particular case, this led to ineffective foreign policy toward China.